Agronomic performance of novel, nitrogen-rich biobased fertilizers across European field trial sites - Müller, Benedikt; Wester-Larsen, Lærke; Jensen, Lars Stoumann; Salo, Tapio; Garrido, Ramiro Recena; Arkoun, Mustapha; D'Oria, Aurélien; Lewandowski, Iris; Müller, Torsten; Bauerle, Andrea (Elsevier, 2024)
Context or problem: Substituting mineral fertilizers with novel biobased fertilizers (BBFs) produced from various organic waste and side streams could contribute to a reduction in the environmental and climate impacts of fertilizer production and use and the recycling of otherwise potentially wasted nutrients. For the substitution to be beneficial for farmers, the environment, and food security, the BBFs need to be effective, reliable and safe. However, the agronomic performance of novel, nitrogen (N) rich BBFs has not yet been well studied. Objectives or research question: The main objective of this study was to determine the agronomic efficiency of N in a relevant range of commercially available BBFs. We hypothesised that they can function as effective substitutes for mineral N fertilizers, independent of the agricultural and geographic settings. Methods: Field trials (fully randomized block design) were conducted at four field sites across Europe covering different climates, soil types, and crop sequences. In total 18 BBFs were tested, 7 of which were common BBFs tested at all sites, while the other 11 (2–3 per site) were local BBFs at individual sites. The design included 4–5 increasing levels of mineral N reference. Trials with BBF application were conducted over 2 years, and the agronomic performance (crop yield and N offtake) was determined to estimate 1st year mineral N fertilizer replacement value (NFRV) in both years, while residual NFRV was estimated only in the 2nd year. Results: The BBFs showed an average N fertilizer replacement value (NFRV) of 70 % across sites and years, with variations in the agronomic performance between the trial sites and years. Compared with the mineral N fertilizer reference applied at the same total N level, no consistent ranking of BBF and no significant differences in yields were found. The BBFs tended to have a higher NFRV when incorporated compared to surface application. Of the 18 BBFs tested, 8 had a NFRV above 75 %, 6 were in the range 60–75 % and 4 were in the low range of 10–60 %. The residual effect of BBFs in the year after application was not significantly higher for any of the BBFs than that of the mineral N fertilizer. Conclusions: Generally, the BBFs performed similar to the mineral reference applied at the same total N level. The performance of BBFs was not significantly affected by climate or soil type. The BBFs appeared to have higher agronomic performance when incorporated into the soil compared to surface application. The second year residual effect of BBF was not significantly higher than that of the mineral reference fertilizer. Implications or significance: In general, most of the investigated BBFs can be considered reasonably effective substitutes for mineral N fertilizers. The results suggest that soil incorporation of BBFs will result in better agronomic performance than surface application.
Keywords: nitrogen; fertilisers; yield; crop